Pre-validation of the WHO organ dysfunction based criteria for identification of maternal near miss - Parpinelli Mary A; Oliveira Neto Antonio F; Souza João P; Cecatti José G; Sousa Maria H; Say Lale; Pattinson Robert C (BMC, 2011)
Abstract Background To evaluate the performance of the WHO criteria for defining maternal near miss and identifying deaths among cases of severe maternal morbidity (SMM) admitted for intensive care. Method Between October 2002 and September 2007, 673 women with SMM were admitted, and among them 18 died. Variables used for the definition of maternal near miss according to WHO criteria and for the SOFA score were retrospectively evaluated. The identification of at least one of the WHO criteria in women who did not die defined the case as a near miss. Organ failure was evaluated through the maximum SOFA score above 2 for each one of the six components of the score, being considered the gold standard for the diagnosis of maternal near miss. The aggregated score (Total Maximum SOFA score) was calculated using the worst result of the maximum SOFA score. Sensitivity, specificity, positive and negative predictive values of these WHO criteria for predicting maternal death and also for identifying cases of organ failure were estimated. Results The WHO criteria identified 194 cases of maternal near miss and all the 18 deaths. The most prevalent criteria among cases of maternal deaths were the use of vasoactive drug and the use of mechanical ventilation (≥1 h). For the prediction of maternal deaths, sensitivity was 100% and specificity 70.4%. These criteria identified 119 of the 120 cases of organ failure by the maximum SOFA score (Sensitivity 99.2%) among 194 case of maternal near miss (61.34%). There was disagreement in 76 cases, one organ failure without any WHO criteria and 75 cases with no failure but with WHO criteria. The Total Maximum SOFA score had a good performance (area under the curve of 0.897) for prediction of cases of maternal near miss according to the WHO criteria. Conclusions The WHO criteria for maternal near miss showed to be able to identify all cases of death and almost all cases of organ failure. Therefore they allow evaluation of the severity of the complication and consequently enable clinicians to build a plan of care or to provide an early transfer for appropriate reference centers.